Zmienność budowy szyszek i powierzchni łusek nasiennych modrzewia europejskiego ( Larix decidua Mill.) - Aniszewska, Monika; Gendek, Arkadiusz; Stadnik, Sylwia (Leśne Prace Badawcze, 2017)
The article describes the shape of cones of European larch ( Larix decidua Mill.) using the fourth-degree polynomial fitting function. The material was derived from the seed orchard of the Barycz Forest District. The curves were used to calculate the area and volume of single cones. It was not possible to generalize the formulas to calculate the surface and volume of larch cones using the described method, due to the large variability of the empirical coefficients of equations. Finally, to calculate the area and volume of cones, the formula to determine the solid figure of cone was used. The constant αs of 0.43 was introduced to the formula. Calculated volume values were compared to actual volumes measured by a water-filled burette. The mean surface area of larch cones was calculated from the forming function and it was 780 mm 2 and the volume was 2434 mm 3 .Values calculated from cone formulas after taking into account the αs and constants (0.68 and 0.53) were 783 mm 2 and 2415 mm 3 , respectively. The outer and inner surfaces of the seed scales coming from the central part of the larch cones were photographed using Quanta 200 scanning microscope. Specific features of the scales were measured using the Multi Scan Base program. It was found that the outer and inner surfaces of the larch scales, such as pine and fir, were different. On the outer side, scales are formed by thick-walled cells with visible protruding trichomes. And on the inside at the location of the wings and seeds are visible thin-walled cells with jagged cell walls. On the surface of the scales, the appearance of long stem cells, resembling threads, that are absent on pine and fir seed scales was observed.